2004
DOI: 10.1007/s00464-004-8802-4
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of laparoscope-assisted surgery for recurrent Crohn's disease

Abstract: Laparoscope-assisted surgery is feasible and advantageous in reoperation for patients with recurrent Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…33 Our conversion rate of 34% was comparable to previous studies. 8,34,35 According to other authors, the main reasons for conversion were the presence of complex inflammatory masses or fistula. 12,36,37 In conclusion, pre-operative management for penetrating CD allowed decreasing dramatically faecal diversion rate compared with the previously reported rate after ICR for penetrating CD with a low rate of post-operative morbidity.…”
Section: Discussionmentioning
confidence: 97%
“…33 Our conversion rate of 34% was comparable to previous studies. 8,34,35 According to other authors, the main reasons for conversion were the presence of complex inflammatory masses or fistula. 12,36,37 In conclusion, pre-operative management for penetrating CD allowed decreasing dramatically faecal diversion rate compared with the previously reported rate after ICR for penetrating CD with a low rate of post-operative morbidity.…”
Section: Discussionmentioning
confidence: 97%
“…The indication for laparoscopy was limited initially to small bowel diseases and localized colonic involvement. Due to the satisfactory outcome of our initial laparoscopic experience [11], the indication for LAP was later expanded to a more challenging procedure (e.g., subtotal or total colectomy). As shown in the current study, however, six attempts at LAP subtotal or total colectomy, even without fistulas or abscesses, resulted in an unacceptably long operative time, suggesting that straight laparoscopic surgery is not a practical solution for that type of disease.…”
Section: Discussionmentioning
confidence: 99%
“…After successful introduction of laparoscopic segmental resection for stricturing Crohn's ileocolitis [11], we began to perform subtotal and total colectomy for Crohn's colitis using laparoscopic technique in 1996. We then began using the HALS technique in 2000.…”
mentioning
confidence: 99%
“…Although some studies have shown that laparoscopic re-resection for Crohn's disease is associated with an increased risk of conversion to open surgery, other studies have shown that conversion from laparoscopic resection for Crohn's disease does not necessarily adversely affect outcome, provided that an appropriate threshold is used to decide when to convert to open surgery. [77][78][79][80][81] Another study of 17 patients with complex Crohn's disease reported a 0% conversion rate from laparoscopic to open ileocolic resection. 82 There is, however, no unequivocal definition of conversion, leading to wide variation in the reported conversion rate.…”
Section: Laparoscopic Surgery For Recurrent and Complicated Crohn's Dmentioning
confidence: 98%